A proposal for the evaluation of multimodal argumentation: Assessing reasonableness and effectiveness in environmental campaign posters - Tseronis, A.; Younis, R.; Üzelgün, M. A. (Journal of Argumentation in Context, 2024)
We argue that the evaluation of multimodal arguments needs to take into account the semiotic resources used to communicate them as well as the context in which they are produced and interpreted. Thus, in addition to the critical questions pertaining to the scheme that help assess the internal cogency of the argument and thereby its reasonableness, we propose asking questions regarding the cognitive and rhetorical dimensions of the argument in order to assess how effectively the semiotic design helps the addressee to process it and how effectively it is adjusted to the audience and context. To illustrate our proposal for a three-dimensional evaluation of multimodal argumentation, we analyze comparatively three environmental campaign posters that present in varying degrees of semiotic complexity the negative consequences of not taking action regarding the protection of the environment.